ANALISIS KINERJA PELAYANAN GARDU TOL PADA JALAN TOL BALI MANDARA - Kencana Dewi, Ayu Indah; Suthanaya, P. Alit; Widana Negara, I.N. (JURNAL SPEKTRAN; Vol 4 No 1 (2016): Vol. 4, No. 1, Januari 2016DO - 10.24843/SPEKTRAN.2016.v04.i01.p01, 2016)
Abstract: At present, thetoll roadhas an important role to serve traffic flow, especiallyin regionsuch asNusaDua.At this time, has not been knowncharacteristics ofvehiclearrivalandserviceoftoll gate. The objectives of this study are: to analyze the characteristics of vehicle arrival rate, to analyze the characteristics of service level toll gate, to analyze the performance of services toll gate and in order to analyze the optimal number of toll gate according to the arrival rate of vehicles at the entrance to the toll road Bali Mandara. Results of analysis showed thatthe characteristics ofvehicle arrivalin cashtoll gateandelectronictoll gatefollowedPoissondistribution. Characteristicstoll gate1, toll gate2andtoll gate3 had a negativeexponentialdistribution. Performance of cashtoll gateservice systemswithdisciplineFVFSqueuewas: =1,131vehicles/min, =0,230vehicles/min, =0,128, and =0,026min. Performanceof electronictoll gateservice systemwithFIFOqueuingdiscipline was: =0,000923vehicles/min, =0,000001vehicles/min, =0,001668minutes, and =0,000002minutes. The results ofthegeneralisedcost analysisforcashtoll gate showedthat optimalconditions for existing vehicle arrivals can be achievedif onlyone toll gate was opened.
Keywords: arrival characteristic, service performance, generalised cost, optimum gate